Neurocysticercosis with initial clinical presentation of acute cysticercal meningitis coexisting with anterior chamber intraocular cysticercosis: a case report from a rural institute in India - Verma, Vijay Kumar; Verma, Archana; Pandey, Pinky; Singh, Brijesh (International Journal of Research in Medical Sciences, 2017)
Acute cysticercal meningitis coexisting with intraocular cysticercosis is an extremely infrequent clinical presentation of neurocysticercosis. We report a 26 year old male, who presented with signs and symptoms of acute eosinophilic cysticercal meningitis with intraocular cysticercosis in the anterior chamber of left eye. Diagnosis was confirmed with demonstration of cerebrospinal fluid (CSF) eosinophilia, cysticercus specific IgG antibodies by CSF ELISA, sterile bacterial, mycobacterial and fungal CSF cultures, cystic lesions containing characteristic scolices consistent with neurocysticercosis on neuroimaging and histopathological demonstration of cysticercus cellulosae larva viscoexpressed from the eye. The importance of having high index of clinical suspicion highlighted along with need of examining cerebrospinal fluid with Wright-Giemsa stain so as not to miss cerebrospinal fluid eosinophilia and diagnosis of this extremely under-reported clinical entity, when there is concurrent presence of brain and other extracerebral lesions consistent with cysticercosis.